Information and Communication Technologies, Prenatal Care Services and Neonatal Health - Diether W. Beuermann; Rafael Anta; Patricia Garcia; Alessandro Maffioli; Jose Perez Lu; Maria Fernanda Rodrigo (Inter-American Development Bank (IDB), 2015)
We evaluate the effectiveness of sending text messages to pregnant women containing appointment reminders and suggestions for healthy behaviors during pregnancy. Receiving messages had an overall positive effect of 5 percent on the number of prenatal care visits attended. Moreover, for women who live close to their assigned health center and who have higher educational attainment, the intervention positively affected vitamin intake compliance, APGAR scores, and birth weight. Evidence suggests that reminders are more effective among those who are more able to understand the future benefits of preventive care (more educated) and who face lower transaction costs of going to prenatal care checkups (located near health centers). No evidence of geographical spillover effects was found.
hdl:11319/6940
Keywords: I10; O12; 330; WAWARED; Peru; e-Health; Pregnancy; Experimental Design